A Vitiation of Pitta Dosha in Sharad Ritu and its Management by Nitya Virechana Dravya (International Journal of Ayurveda and Pharma Research, 2024)
Pama Kushta is explained in Ayurveda which is outcome of Pitta Dosha Dushti it has similarities with eczema. Eczema is a chronic inflammatory skin condition characterized by redness, itching, and rash, affects a significant portion of the population worldwide. This case report presents the initial successful management of eczema in a patient using Ayurvedic interventions. A 30-year-old female patient presented with persistent eczema symptoms on her arms and legs. The patient underwent a thorough evaluation based on Ayurvedic principles, which identified imbalances in Doshas (bioenergies) according especially in autumn season and suggested a treatment plan accordingly. The interventions included internal medications to alleviate imbalances Pitta Dosha, external application of Marichyadi Oil to soothe the affected areas. After adhering to the treatment plan for two weeks, the patient experienced a significant reduction in eczema symptoms, including reduced redness, itching, and improvement in skin texture. This case report highlights the potential efficacy of Ayurvedic interventions with Siddhanta. The holistic approach of Ayurveda, addressing root cause, resulted in improved symptom control and enhanced quality of life for the patient. While further research is warranted to validate these findings, the present report suggests that Ayurveda could be a valuable complementary approach for individuals struggling with eczema. Health professionals and patients alike may consider exploring Ayurvedic interventions as an adjunct or alternative to conventional eczema management strategies.